High-resolution body wave tomography beneath the SVEKALAPKO array: II. anomalous upper mantle structure beneath the central baltic shield - Sandoval, Senén; Kissling, Eduard; id_orcid:0 000-0001-9575-7951; Ansorge, Joerg (Wiley-Blackwell, 2004)
ISSN:0956-540X ISSN:1365-246X